Voices from the Sea: Empowering Maritime Cadets through Industry-Based Internships for Sustainable Port Management - Silalahi, Aliong; Saifudin, Iksan; Alamsyah, Jaya (Pusat Penelitian dan Pengabdian kepada Masyarakat (P3M) STIP Jakarta, 2025)
This study investigates the role of year-long industry-based internships in shaping the competencies of maritime cadets in sustainable port and shipping management. Conducted with fifteen seventh-semester cadets from the Maritime Polytechnic of North Sulawesi, complemented by insights from five maritime professionals and five academic lecturers, this qualitative research highlights the experiential learning that occurs within real-world maritime settings. Cadets engaged in internships across port offices, shipping companies, and marine industries, applying classroom knowledge to operational tasks involving logistics, regulatory compliance, and environmental monitoring. The findings indicate that prolonged exposure to industry practices fosters not only technical proficiency but also a nuanced understanding of sustainability issues in maritime operations. Furthermore, mentorship from professionals and feedback from academic supervisors bridge theoretical knowledge with applied action. The study advocates for internship programs to be more systematically integrated into vocational curricula as a transformative educational tool for maritime sustainability and social responsibility.